PEMBUATAN PAPAN ISOLASI DARI CAMPURAN PULP LIMBAH PEMBALAKAN HUTAN DAN ARANG AKTIF DENGAN BAHAN PEREKAT KHITOSAN CANGKANG UDANG - Han Roliadi; Rena M Siagian; Dian Anggraini Indrawan; Rosi M. Tampubolon (Jurnal Penelitian Hasil Hutan, 2012)
This study examined characteristics of insulation board manufactured from the mixture of wood astes from Eucalyptus bybrid plantation forest (PF) logging and activated charcoal, and the adhesive as used was chitosan derived from the shrimp exoskeleton. PF-logging's wood wastes were reduced in size to chips, then made into pulp using open bot soda chemical process at the condition being alkali (NaOH) concentration at 8%, wood to liquor ratio 1:8 (w/v), and maximum cooking temperature 100C held for 3 hours. Insulation-board mat was formed using the wet process from the miscture of PF logging's wood wastes and activated charcoal at the proportions (w/w) consecutively 100% +0%, 97,5% + 2,5%, 95% + 5%, 92,5% +7,5%, dan 90%+10%. Prior to mat forming, to the miscture were added 2 kinds of adhesives separately (i.e. chitosan and tapioca as the comparison) 5% each. Physical and mechanical properties of the resulting insulation board with tapioca were better than those with chitosan. The greater the portion of activated charcoal mixed to the PF-logging's wood wastes, the lower the density and the strength (MOR), the more increased the moisture content, but the more improved the dimensional stability. The insulation board which revealed the most promising prospects and could favorably meet the JIS specification was the one from the mixture proportion of PF-logging's wood wastes and activated charcoal at 97.5%+ 2.5%, uring tapioca adhesive, and the one from solely 100% PF-logging wastes (without activated charcoal) using chitosan.